Revitalization Of The Sukawati Art Market From An Urban Tourism Planning Perspective: Integrating Cultural Preservation And Sustainable Tourism - Anak Agung Anggia Dyah Gardewi; Nyoman Diah Utari Dewi; I Wayan Astawa (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2026)
Traditional art markets are being revitalized as a strategy to enhance cultural tourism while preserving local heritage. This study examines the revitalization of the Sukawati Art Market through urban tourism planning. A qualitative approach was employed, utilizing the Systematic Literature Review (SLR) method in accordance with the PRISMA 2020 guidelines. To this end, an extensive review of the extant literature was conducted, encompassing publications from 2015 to 2025. This review encompassed a wide array of sources, including Scopus, ScienceDirect, SpringerLink, Taylor & Francis, Google Scholar, and SINTA. The collected data was then subjected to a rigorous thematic content analysis. The findings indicate that the revitalization of the Sukawati Art Market has improved physical infrastructure, visitor comfort, accessibility, and destination competitiveness while strengthening the creative economy and supporting local artisans. The study also reveals that revitalization can generate economic benefits without undermining cultural authenticity when supported by appropriate governance and community participation. From the perspective of urban tourism planning, the successful revitalization of a destination integrates spatial planning, cultural heritage preservation, tourism management, and environmental sustainability to create a more competitive and resilient destination. The study proposes an integrated revitalization model that connects destination management, cultural preservation, creative economic development, and sustainable tourism. The revitalization of the Sukawati Art Market promotes inclusive, culturally sensitive, and sustainable urban tourism. Consequently, this model has the potential to offer practical guidance for the revitalization of traditional art markets in other cultural tourism destinations.